The comparative estimation of influence of higholeic sunflower and palm oils consumption on the fatty acids content of rat liver lipids - Levitsky, A. P.; Khodakov, I. V.; Tkachuk, V. V. (Journal of Education, Health and Sport, 2017)
Aim: To determine of influence of higholeic sunflower and palm oils consumption on the fatty acids content of rat liver lipids. Materials and methods: The content of liver lipids and fatty acid levels in 2 lipid fractions were determined in 3 groups of rats: 1 – fat fee ration, 2 – ration with 15 % higholeic sunflower oil and 3 – ration with 15 % palm oil. The duration of feeding was 40 days. First lipid fraction was triglycerides (TG) + ester cholesterine (EC). Second lipid fraction was free fatty acids (FFA). Results: Increase of weight was the largest for third group, and the least for second group. The content of lipids in liver was the largest for third group, and the last for first group. The content of FFA was the largest for third group. The content of ω-6 PUSFA was the largest for third group. The content ω-3 PUSFA was the largest for second group. Conclusion: Palm oil consumption leact to increase sueight, the content of lipids and ω-6 PUSFA or decrease the content of ω-3 PUSFA on liver. Higholeic acid sunflower oil increase the content of ω-3 PUSFA.